Evaluasi Kualitas Organoleptik Mayonnaise Berbahan Dasar Kuning Telur yang Mendapatkan Suplementasi Tepung Purslane (Portulaca oleracea) - Kartikasari, L. R.; Hertanto, B. S.; Nuhriawangsa, A. M. P. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
The aim of this research was to evaluate sensory quality of mayonnaise made with egg yolks produced from laying hens fed diets supplemented with purslane meal. The experimental design was a one way classification with five mayonnaise treatments. The treatments included mayonnaise with egg yolks supplemented with 0% (P0), 2% (P1), 4% (P2), 6% (P3), and 8% (P4) purslane meal. This study used 30 semi-trained panelists to evaluate sensory quality of mayonnaise using a 9-point hedonic scale. Data was analysed using the analysis of variance and if there was any significant difference among treatments, then the analysis was continued using Tukey’s test. The results showed that the use of egg yolks from laying hens fed diets supplemented with purslane meal up to a level of 8% did not significantly change color, texture, creamy, aroma, taste, taste and overall acceptance of mayonnaise. The average score of perception of sensory attributes was between 5 (neither like nor dislike) and 6 (slightly like). It can be concluded that mayonnaise made with egg yolks produced from brown laying hens fed diets supplemented with purslane meal up to a level of 8% did not negatively affect the sensory quality of mayonnaise.